Konsep Pluralisme Agama Dalam Al-Qur’an: Studi Komparatif Tafsir Fi Zilal Al- Qur’an dan Tafsir Al-Mishbah - Fadlilah, Alfan Zamzami; Rohman, Ali Abdur (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2024)
This research is motivated by the concept of religious pluralism which is a debate about its meaning and essence and application in social life. In a plural society like in Indonesia, an attitude of mutual tolerance is needed for each other called pluralism. So religious pluralism is an attitude of mutual respect for the beliefs of other groups. This research aims to review how the concept of religious pluralism through the interpretation of the Qur'an is by describing the interpretation of Sayyid Qutb in the Tafsir Fi Zilal al-Qur'an and Quraish Shihab in the Tafsir al-Mishbah regarding verses related to religious pluralism. And also analyze the comparison of the interpretations of the two figures. In conducting the research, the author used a comparative analysis method, and in collecting data using the library research method (Library Research). The results of the study show in the interpretation of the two figures in the first verse about religious plurality, the second verse about religious freedom, and the third verse about maintaining attitudes to other groups. The two have differences, including in interpreting shabi'in, there are also differences in mufassir tendencies due to his different social context where Sayyid Qutb is more towards proselytizing while Quraish Shihab is more towards humanity. These two interpretations both use the tahlili method, patterned al-adabi al-ijtima'i, and sourced from the narration (bil-Ma'tsur). In essence, in the interpretation of the two figures, it shows that Islam teaches the values of pluralism, namely recognizing plurality, being tolerant, upholding human rights, and maintaining speech and behavior towards other groups.